2018
DOI: 10.1007/s11165-018-9793-9
|View full text |Cite
|
Sign up to set email alerts
|

A Fragmented Training Environment: Discourse Models in the Talk of Physics Teacher Educators

Abstract: This article reports the results of an empirical study exploring the discourses of physics teacher educators. We ask how the expressed understandings of a physics teacher education programme in the talk of teacher educators potentially support the identity construction of new teachers. Nine teacher educators from different sections of a physics teacher programme in Sweden were interviewed. The concept of discourse models was used to operationalise how the discourses of the teacher education programme potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…The study reported in this paper is based on eleven interviews with physics lecturers who work with trainee physics teachers at four separate universities in Sweden. Building on the findings of our earlier work (Larsson et al, 2020) we return to our original three interviews with physics lecturers and combine these with a further eight interviews with physics lecturers who teach physics to trainee teachers at three additional Swedish universities of varying size and research orientation.…”
Section: The Two Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported in this paper is based on eleven interviews with physics lecturers who work with trainee physics teachers at four separate universities in Sweden. Building on the findings of our earlier work (Larsson et al, 2020) we return to our original three interviews with physics lecturers and combine these with a further eight interviews with physics lecturers who teach physics to trainee teachers at three additional Swedish universities of varying size and research orientation.…”
Section: The Two Data Setsmentioning
confidence: 99%
“…] promote teaching as an intellectually challenging endeavor" (T-TEP, 2012, p. 23). In our earlier work, we focused on the Swedish system of physics teacher education (Larsson et al, 2020) and examined the differences in how educators working in the different parts of an educational program, (physics department, education department and school), expressed what they saw as valued and important in their practices. Analysis resulted in the construction of four discourse models-tacit, default positions about the overarching goal of the program adopted by the training staff interviewed.…”
Section: Introductionmentioning
confidence: 99%
“…While the quantum mechanics course does not include the teaching and learning of physics as a course content, what is explicitly and implicitly communicated about teaching and learning is highly relevant for the future physics teachers. This is particularly interesting as previous research show that physics teacher education is often fragmented, as different departments are responsible for different parts of the education (Larsson et al 2018). It is in the light of the need to create a better continuity across different part of the physics teacher education (Sandifer and Brewe 2015) we discuss the potential consequences of our findings for teacher education.…”
Section: Introductionmentioning
confidence: 73%
“…Thus, what is communicated about the teaching and learning of physics in the course is highly relevant for these teacher trainees, even if physics teaching methods are not an explicit part of the course content. Previous research has noted that physics teacher education is often fragmented, given that the content courses are taught by physics departments and the pedagogical courses by departments of education, something that is considered problematic (Larsson et al 2018). A factor that has been suggested as important for high-quality physics teacher education is the collaboration between physics departments and education departments (Sandifer and Brewe 2015, p. 3).…”
Section: Consequences For Physics Teacher Educationmentioning
confidence: 99%
See 1 more Smart Citation